2023
DOI: 10.3390/antibiotics12040668
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antibiofilm Activity of Colombian Essential Oils against Different Candida Strains

Abstract: Most Candida species are opportunistic pathogens with the ability to form biofilms, which increases their resistance to antifungal drug therapies and the host immune response. Essential oils (EOs) are an alternative for developing new antimicrobial drugs, due to their broad effect on cellular viability, cell communication, and metabolism. In this work, we evaluated the antifungal and antibiofilm potential of fifty EOs on C. albicans ATCC 10231, C. parapsilosis ATCC 22019, and Candida auris CDC B11903. The EOs’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…These essential oils, rich in compounds such as carvacrol and thymol, show effectiveness against the growth of Candida, both in its planktonic and sessile forms. A reduction in hyphae production was also observed, suggesting its therapeutic potential in the treatment against Candida spp (Ruiz-Duran et al, 2023).…”
Section: Essential Wrist Oilsmentioning
confidence: 88%
“…These essential oils, rich in compounds such as carvacrol and thymol, show effectiveness against the growth of Candida, both in its planktonic and sessile forms. A reduction in hyphae production was also observed, suggesting its therapeutic potential in the treatment against Candida spp (Ruiz-Duran et al, 2023).…”
Section: Essential Wrist Oilsmentioning
confidence: 88%
“…Researchers have carried out extensive investigation into the antifungal properties of EOs obtained from a range of plant-based sources. [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. These EOs encompass a wide array of bioactive compounds and exhibit potent antimicrobial activity against C. auris .…”
Section: Eos and Their Compounds Against C Aurismentioning
confidence: 99%
“…A total of 81 compounds were identified and quantified (>0.1%) in the EOs, and their relative abundances were grouped by chemical class as sesquiterpene hydrocarbons (43%, SH), followed by monoterpene hydrocarbons (17%, MH), oxygenated monoterpenes (16%, OM), oxygenated sesquiterpenes (16%, OS), and oxygenated compounds (8%, OC) (Table S1) [18].…”
Section: Plant Materials and Chemical Analysis Of Essential Oilsmentioning
confidence: 99%
“…The EOs used in this study were previously reported by [18]. The EOs used were characterized and supplied by the National Center for Research on Agro-Industrialization of Tropical Medicinal Aromatic Plants (CENIVAM), at the Universidad Industrial de Santander (Bucaramanga, Colombia).…”
Section: Plant Materials and Characterization Of Essential Oilsmentioning
confidence: 99%